Application of Plant Growth Regulators During Early Fruit Development Stage Increased Perceived Sweetness of Mango Fruit - Li Li; Xiaowei Ma; Songbiao Wang; Chi Xu; Hongxia Wu; Yanke Wu; Yingzi He; Bin Zheng; Qingzhi Liang; Wentian Xu; Weiming Li (Horticulturae)
This study investigated the optimal strategies for improving sugar biosynthesis in mango fruits. Randomized block design was used for experimental treatments. The mango cultivar “Renong-1” was sprayed with five green plant growth regulators, including solutions of SBP (sucrose-based polymers, a new highly efficient and eco-friendly plant growth regulator), SPM (sucrose + potassium dihydrogen phosphate + microelement fertilizer), TPM (taurine + potassium dihydrogen phosphate + microelement fertilize), PFA (potassium fulvic acid), and SOP (seaweed oligosaccharide peptide) at different fruit development stages. Indicators, such as soluble solid content, soluble sugar and starch contents, and activities of 11 enzymes associated with sugar metabolism in physiologically mature and in full ripening fruits were evaluated. The results showed that SBP solution diluted 100-fold exerted the strongest effect on the soluble sugar content and sweetness value of “Renong-1” mango fruits. Based on the linear regression analysis, a significant negative correlation was observed between the activity of acid invertase and the perceived sweetness of physiologically mature fruits, while the activities of other enzymes were significantly negatively correlated with the perceived sweetness of full ripening fruits. According to multiple regression (by lars function in R) and other comprehensive analysis, A1B3 (spraying SBP solution one time in the young fruit stage) was selected as the optimal treatment combination for enhancing “Renong-1” mango perceived sweetness, followed by A1B2 (spraying SBP solution for the first time in the young fruit stage and the second time at medium maturity) as the alternative treatment combination.